2014
DOI: 10.1136/gutjnl-2013-306347
|View full text |Cite
|
Sign up to set email alerts
|

ER stress induces epithelial differentiation in the mouse oesophagus

Abstract: These results show that ER stress induces epithelial differentiation in precursor cells in the oesophageal epithelium. This UPR induced differentiation may serve as a quality control mechanism that protects against oesophageal cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
5
22
0
Order By: Relevance
“…Changes of ER morphology can occur without ER stress (English and Voeltz, 2013), and some molecular actors that sign ER stress are not detected in Elp3cKO cortices. Indeed, UPR also works as a physiological homeostat that balances the cell's protein folding capacity with its needs and recent works support its active contribution to cell differentiation in distinct tissues (Heijmans et al, 2013;Rosekrans et al, 2015). We found that exacerbated transduction through the PERK-eiF2a UPR branch-also used by differentiating intestinal stem cells (Heijmans et al, 2013)-interferes with cortical neurogenesis in Elp3cKO embryos.…”
Section: Dynamic Regulation Of Upr Controls Neurogenesis In the Develmentioning
confidence: 53%
“…Changes of ER morphology can occur without ER stress (English and Voeltz, 2013), and some molecular actors that sign ER stress are not detected in Elp3cKO cortices. Indeed, UPR also works as a physiological homeostat that balances the cell's protein folding capacity with its needs and recent works support its active contribution to cell differentiation in distinct tissues (Heijmans et al, 2013;Rosekrans et al, 2015). We found that exacerbated transduction through the PERK-eiF2a UPR branch-also used by differentiating intestinal stem cells (Heijmans et al, 2013)-interferes with cortical neurogenesis in Elp3cKO embryos.…”
Section: Dynamic Regulation Of Upr Controls Neurogenesis In the Develmentioning
confidence: 53%
“…In another study, Ah1-Cre mediated GRP78 knockout in intestine led to induction of ER stress, loss of selfrenewal capacity and rapid repopulation of wild-type stem cells (Heijmans et al, 2013). This same study also showed Ah1-Cre activity in esophagus, and GRP78 null esophageal epithelial cells lost their proliferative capacity and were replaced by unrecombined GRP78-positive cells (Rosekrans et al, 2014).…”
Section: Intestine and Esophagusmentioning
confidence: 77%
“…Consistent with this, the small intestine, which contains high numbers of Paneth cells, has higher baseline levels of UPR-related gene expression than the colon [9]. The UPR is not only of importance to the function of differentiated IEC subtypes but also gut stem cells in general as ER stress and UPR induction are critical to such cells in the intestine [10 ▪ ] and oesophagus [11]. Given these broad biologic effects and evidence that UPR-related genetic risk loci are associated with inflammatory bowel disease (IBD), it is important to understand how these pathways operate in the maintenance of intestinal homeostasis and disease.…”
Section: Introductionmentioning
confidence: 89%